Design and modeling of InGaAs/GaAsSb nanoscale heterostructure for application of optical fiber communication system. (2020) - Vijay, Jayprakash; Yadav, Radha krishan; Alvi, P.A.; Singh, Kulwant; Rathi, Amit
Abstract: In this paper, we have designed and theoretically analyzed InGaAs/GaAsSb nanoscale heterostructure, where InGaAs is quantum well material and GaAsSb is the barrier material. The proposed design is modeled using the 6 band k.p. method to find the wave functions and optical gain. An optical gain of 6220/cm is obtained at 1550 nm wavelength. The entire structure has been modeled on the GaAs substrate at room temperature 300 K. Due to the low attenuation of silica made optical fiber at 1550 nm wavelength, the designed heterostructure can be used for fiber optics applications.